Theological Influences on Religious Perceptions in South Sulawesi: A Mashlahah-Based Study of the FKUB - Saleh, Marhaeni; Rahmawati, Rahmawati; Abubakar, Muhammad bin (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
This article explores the influences of purificative theology on the interpretation of religious teachings, with a particular focus on the Interfaith Communication Forum (FKUB) in South Sulawesi, Indonesia. As a descriptive qualitative study, it examines the perspectives of interfaith leaders, highlighting how religious understanding is shaped by individual and institutional theological interpretations. The research employs a theological framework grounded in the maqasid al-shariah (objectives of Islamic law), utilizing in-depth interviews and literature analysis as primary data collection methods. Informants include FKUB leaders, Islamic scholars (ulama), and Christian pastors. The FKUB plays a vital role in promoting religious harmony in Indonesia by facilitating dialogue among leaders of different faiths. Findings reveal that theological orientation significantly affects religious understanding, encompassing tendencies such as puritanism, exclusivism, inclusivism, fundamentalism, and moderation. In this context, the FKUB promotes an inclusive and moderate theological stance that encourages interfaith dialogue, mutual respect, and the preservation of religious diversity. Members of the FKUB engage in open discussions, seeking shared values while upholding their own beliefs. From the perspective of Islamic law, such inclusivity aligns with the concept of mashlahah (public benefit), fostering social harmony and ensuring the well-being of the broader society. This approach helps sustain a tolerant and peaceful religious environment in Indonesia.